Governmental Accounting: A Critical Evaluation. - Neeley, Paden; Robason, C. A. (The Accounting Review, 1967)
This article presents a critical evaluation of the accounting curriculum by both accounting educators and practitioners. A survey was made of accounting professors throughout the nation. The specific objectives of this study were, first, to determine what is presently being done with respect to governmental accounting in the curriculum and second, to determine the opinions held by accounting professors of the value of a course in governmental accounting. This report is based on the above mentioned survey, in which a questionnaire was mailed to one accounting professor at each of the 105 member schools of the American Association of Collegiate Schools of Business. Results indicate, two schools indicated they had recently moved the course to a graduate level elective. Two schools had eliminated it and moved the area of fund accounting to another course. One school had removed it from its day program but continued to offer it at night. One school had replaced governmental accounting with a required course in accounting systems and data processing and one school was offering the course this year for the first time in ten years.